Functional diversity of the glutathione peroxidase gene family among human populations: implications for genetic predisposition to disease and drug response. (July 2013) - Polimanti, Renato; Fuciarelli, Maria; Destro-Bisol, Giovanni; Battaggia, Cinzia
Aim: To analyze the human genetic variation of glutathione peroxidases (GPX), estimating the functional differences among human populations and suggesting interethnic differences in predisposition to disease and drug response.Materials & methods: Using 1000 Genomes Project data, we analyzed 723 GPX variants in 1092 individuals belonging to 14 populations. Combining functional prediction analyses of coding and noncoding variants, we developed a method to estimate haplotype functionality.Results: GPX rare variants have a higher functional impact than common variants. The frequency among Asian patients of haplotypes associated with normal functionality is significantly higher for GPX1 and lower for GPX3 than for non-Asian patients; no adaptation signals in GPX1 and GPX3 were found in Asian patients.Conclusion: GPX1 and GPX3 differences may be associated with alterations in antioxidant capacity and redox regulation, which suggests diverse susceptibility to complex disease and diverse response to relevant drugs in Asians compared with individuals with other ethnic origins. Original submitted 7 February 2013; Revision submitted 16 May 2013